Blaschko-linear acquired dermatitis. Case report. - Corradin, T.; Fiorentino, R.; Tositti, L.; Belloni-Fortina, A. (European Journal of Pediatric Dermatology, 2011)
Here we present the case of a 52 year-old woman with erythematous, scaly, non itching papules disposed unilaterally along the Blaschko lines on the left side of the trunk, on the left arm and leg. This case, which shares histological and clinical characteristics with both lichen striatus and adult blaschkitis, should be included in the group of other diseases presenting with linear pattern and defined BLAISE (Blaschko-Linear Acquired Inflammatory Skin Eruption) by Taïeb et Al. (19) and more recently ABLD (Acquired Blaschko-Linear Dermatoses) by Keegan et Al. (10).